A Japanese version of the Patient Attitudes and Beliefs Scale for patients with musculoskeletal disorders. (1st December 2020) - Takasaki, Hiroshi; Hall, Toby
ABSTRACT: Background : The Patient Attitudes and Beliefs Scale (PABS) is a self-reporting questionnaire with 12 items on a 5-point Likert scale for patient's attitude towards shared decision making but its adaptation into Japanese has not been undertaken. Objectives : To develop a Japanese version of the PABS (PABS-J) through translation into Japanese and evaluation of an appropriate scoring system and unidimensionality using Rasch analysis and test–retest reliability. Design : This study included a cross-cultural validation step and investigations of questionnaire validity and reliability. Method : One-hundred-ten patients with musculoskeletal disorders referred to physiotherapy completed the Japanese draft of the PABS before the initial session of physiotherapy. Seventy-five of the 110 participants completed the PABS twice, on a separate day. Items that violated pre-determined criteria of unidimensionality and test–retest reliability (Quadratic-weighted κ ≦ 0.4) were removed. Further, the 110 participants identified one of the four stages of readiness towards shared decision making and correlation with the score of the PABS-J was preliminarily investigated as concurrent validity. Results/Findings : Rasch analysis confirmed unidimensionality of six items and appropriateness of a 3-point scale. Moderate test–retest reliability of the PABS-J was detected (Intra-class correlation coefficient = 0.70). A statistically significant and positive but weak correlation between the PABS-J scores and the four stages of readiness towards shared decision making was detected ( ρ = 0.20, P = 0.03). Conclusions : The current study demonstrated partial validity and reliability of the PABS-J with six items and 3-point scale. This questionnaire will be a foundation for further investigations attitude towards shared decision making.